Two-body dry abrasive wear performance of high velocity oxygen fuel spray process and electrodeposited cermet coatings - Mohd Rabani, Nur Amira; Kamdi, Zakiah (Trans Tech Publications, 2017)
In order to protect parts against wear, the carbon steel used are commonly coated by cermet coatings to increase the wear resistance. In this paper, the coatings consist of tungsten carbide 17 wt% cobalt (WC-17Co), tungsten carbide 9 wt% nickel (WC-9Ni), electrodeposited nickel (electro Ni) and electrodeposited nickel-silicon carbide (electro Ni-SiC) coatings. All coatings are deposited onto AISI 1018 carbon steel by using two different methods which are high velocity oxygen fuel (HVOF) and co-electrodeposition method. Abrasive wear test were observed under two-body dry abrasion conditions with pin-on-disc test arrangement. Based on the volume loss after the wear test, the wear rates were calculated by using Archard’s law. The wear tracks were investigated by using scanning electron microscope (SEM) and atomic force microscopy (AFM). The hardness of each coating was measured by using Vickers microhardness. The results showed that HVOF coatings have lower wear rate compared to the electrodeposited coatings. WC-9Ni has the lowest wear rate which is 4.06×10-3 mm3/Nm much lower compared to electro Ni-SiC of 16.36×10-3 mm3/Nm. This result was expected as the hardness of WC-9Ni is 1625.37 HV higher than electrodeposited coatings which approximately 380.51 HV. In conclusion, the methods of coating deposited affect the wear resistance as well as the hardness of the coatings.